Promoting the Cultural Understanding of a Student in a General Education School: Teachers’ Experiences and Challenges - Briška, Ilze; Siliņa-Jasjukeviča, Gunta (Acta Paedagogica Vilnensia, 2020)
Cultural understanding is a basis for competence-oriented general education. Teachers are responsible for applied content and methods that are used to purposefully lead school students to that result.The aim of this study is to identify actual goals for the development of teacher education curriculum, professional development, and teaching aids by investigating in-service teachers’ challenges in the successful promotion of students’ cultural understanding in general schools.The readiness of teachers to promote the cultural understanding of primary school students was explored in a mixed-methods study. The findings indicated aspects that teachers consider relevant as well as the main problems and gaps between theoretical principles recognised as essential by educational policy, and teachers’ beliefs and practices.
Keywords: cultural understanding; general education; teachers’ experience; mixed-methods study